Dinamika Penyelesaian Sengketa Dagang Komoditas Baja Indonesia Melalui Wto Terhadap Uni Eropa - Hafiz Hairullah (Riviera Publishing, 2025)
This research explores Indonesia's role as a major player in the global steel and iron export market, particularly in relation to the European Union (EU). As the fifth largest exporter of steel and iron by 2022, Indonesia has seen its exports increase dramatically from US5.60 billion in 2018 to US27.82 billion in 2022. However, Indonesia faces significant trade barriers, including anti-dumping and safeguard duties imposed by the European Union. This article highlights the complexities of dealing with dumping allegations, with reference to Indonesia's experience with the World Trade Organization (WTO) and its diplomatic efforts in trade disputes with countries such as Australia and Pakistan. The WTO Dispute Settlement Body (DSB) plays an important role in resolving these conflicts, providing a framework for fair trade practices. In addition, the article also discusses the current challenges Indonesia faces regarding low-grade stainless steel products and emphasizes the need for effective government diplomacy. By engaging industry, society, and academia, the Indonesian government can improve its position in international trade. Through diplomacy and strategic collaboration, Indonesia aims to overcome trade barriers and promote its industrial interests globally.